MODERN METHODS OF TEACHING ENGLISH - Umirxon Odilovna Azimova (Web of Journals Publishing, 2023)
This article analyzes the opinions and scientific views of scientists and pedagogues regarding the use of new pedagogical methods in teaching English, in particular, interactive methods and the scientific-theoretical aspects of the factors that arouse students' interest in learning this language, and their subjective attitude to them attitude expressed.
Keywords: interactive methods, role-playing games, brainstorming, case-study, innovative technologies, intellectual activity.